Knowledge Relates to People’s Attitudes - PH, Livana; Kuncoro, Amin; Suerni, Titik (Journal of Economics and Public Health, 2023)
Coronavirus Disease 2019 (Covid-19) has become a pandemic worldwide, including in Indonesia. The transmission of Covid-19 in Indonesia is very fast and affects 34 provinces, many of which are in red zones. Central Java is one of the provinces with a very fast Covid-19 transmission. Public knowledge and attitudes towards the Covid-19 pandemic are very important to reduce the risk of infection among the community. The purpose of this study was to knowledge is related t people’s attitudes. The research design used was descriptive analitik with cross sectional approach, with a sample size of 65 respondents who were selected using the random sampling method. Data collection used a google form questionnaire and analyzed using Chi-Square. The results showed knowledge is related to people’s attitudes with a p value (0.000). Good knowledge and a positive attitude from the public in dealing with the Covid-19 pandemic can make people take real action to reduce the risk of contracting Covid-19.